Does Being Included in The Sustainability Index Affect Financial Performance and Firm Value? Evidence From Borsa Istanbul - Yilmaz-Ozekenci, Sureyya; Topaloglu, Emre Esat (Sosyoekonomi Soc, 2025)
This study investigates the effect of being included in the Borsa Istanbul Sustainability Index on financial performance and firm value. The company data contained in the BIST Sustainability Index for 2018Q1-2023Q3 are analysed with the Driscoll-Kraay estimator. According to the results of Model A, it is understood that the inclusion of the company in the sustainability index does not have a significant effect on financial performance, while according to Model B, it is understood that the inclusion of the company in the sustainability index has a positive and significant impact on firm value. The publication of sustainability reports by enterprises in the sustainability index conveys more accessible information to investors. Investigating the effect of being included in the sustainability index on firm value reveals the originality of this study.
Keywords: Sustainability Index; Financial Performance; Firm Value